The impact of ethics and fraud pentagon theory on academic fraud behavior - Wira Utami, Dhita Permata; Purnamasari, Dian Indri (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2021)
This study aims to determine the impact of ethics, pressure, opportunity, rationalization, competence, and arrogance on accounting students' academic fraud behavior. The population of this research consists of UPN